Technical Guidance on Shredded Cattle Meat for Strengthening the Entrepreneurship for New Graduates - Hafid, Harapin; Nuraini, Nuraini; Inderawati, Inderawati; Ananda, S.H.; Sani, L.O.A. (Talenta Publisher Universitas Sumatera Utara, 2020)
Community service activities in the form of training in the application of appropriate technology for shredded production aimed at providing entrepreneurial skills and motivation. In this activity, technical guidance is carried out to increase knowledge and skills as well as work insights to the target so that they can form a shredded meat business group so that they can supply shredded needs for the people in the city of Kendari and surrounding areas. The activity method uses the technical guidance method where the participants are first given counseling related to basic knowledge of raw materials, equipment, manufacturing processes and abon assessment. Then there was a demonstration to make floss making involving the participants. The results achieved in this activity, in the form of increased knowledge and understanding of the training participants consisting of alumni of the Department of Animal Science, Halu Oleo University, were very interested and enthusiastic about receiving training materials and were very actively participating in the training activities. This situation shows that alumni majoring in animal husbandry are still in dire need of additional practice material because of the limited practical opportunities they have. In evaluating activities, participants' perception responses to follow-up activities are divided into three categories. Most want to make it for consumption and sell it as a source of income (60%), some want to make it for their own consumption with their families (30%) and some are interested but it is difficult to buy raw meat because of economic incapability (10%).